NEBIVOLOL, BUT NOT METOPROLOL, LOWERS BLOOD PRESSURE IN NITRIC OXIDE-SENSITIVE HUMAN HYPERTENSION - Okamoto, Luis E. (Hypertension, 2014)
Nebivolol, unlike other selective β(1)-receptor blockers, induces vasodilation attributable to increased nitric oxide (NO) bioavailability. The relative contribution of this mechanism to the blood pressure (BP) lowering effects of nebivolol is unclear because it is normally masked by baroreflex buffering. Autonomic failure provides a unique model of hypertension devoid of autonomic modulation but sensitive to the hypotensive effects of NO potentiation. We tested the hypothesis that nebivolol would decrease BP in these patients through a mechanism independent of β-blockade. We randomized 20 autonomic failure patients with supine hypertension (14 men, 69±2 yrs.) to receive a single oral dose of placebo, nebivolol 5 mg, metoprolol 50 mg (negative control) and sildenafil 25 mg (positive control) on separate nights in a double-blind, crossover study. Supine BP was monitored every 2 hours from 8pm to 8am. Compared to placebo, sildenafil and nebivolol decreased systolic BP (SBP) during the night (P<0.001 and P=0.036, by mixed-effects model, maximal SBP reduction 8-hours postdrug of −20±6 and −24±9 mm Hg, respectively), whereas metoprolol had no effect. In a sub-analysis, we divided patients into sildenafil responders (BP fall >20 mmHg at 4am) and non-responders. Nebivolol significantly lowered SBP in sildenafil responders (−44±13 mmHg) but not in non-responders (1±11 mm Hg). Despite lowering nighttime BP, nebivolol did not worsen morning orthostatic tolerance compared with placebo. In conclusion, nebivolol effectively lowered supine hypertension in autonomic failure, independent of ß(1)-blockade. These results are consistent with the hypothesis that NO potentiation contributes significantly to the antihypertensive effect of nebivolol.